Biomechanical responses of thigh and lower leg during 10 consecutive soccer instep kicks - Amiri-Khorasani, M.; Abu Osman, N. A.; Yusof, A. (The Journal of Strength and Conditioning Research, 2011)
This study investigated the number of trials necessary to obtain optimal biomechanical responses in 10 consecutive soccer instep kicks. The kicking motions of dominant legs were captured from 5 experienced and skilled adult male soccer players (height: 184.60 ± 4.49 cm; mass: 80 ± 4.24 kg; and age: 25.60 ± 1.14 years) using a 3D infrared high-speed camera at 200 Hz. Some of the important kinematics and kinetics parameters are maximum thigh angular velocity, maximum lower leg angular velocity, maximum of thigh moment, maximum lower leg moment at forward and impact phases, and finally maximum ball velocity after impact selected to be analyzed. There was a significant decrease of ball velocity between the first and the fifth kick and the subsequent kicks. Similarly, the lower leg angular velocity showed a significant decrease after the fifth kick and thereafter. Compared with the first kick, the thigh angular velocity has been shown to decrease after the sixth kick and thereafter, and the thigh moment result of the sixth kick was significantly lower when compared with the first kick. Moreover, the lower leg moment result of the fourth kick was significantly lower in comparison with the first kick. In conclusion, it seems that 5 consecutive kicks are adequate to achieve high kinematics and kinetics responses and selecting more than 5 kicks does not result in any high biomechanical responses for analysis.